The Politics of memory and place-making in local opera: The case of the Kymi River Opera - Hautsalo, Liisamaija; Westerlund, Heidi (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2023)
This case study on the Kymi River Opera in south-eastern Finland, at the former border between Sweden and Russia, explores the potential of local operas to re-create a sense of place identity in a contemporary society in which people often seek to reconstruct identity through place memory. By engaging with Christopher Small’s (1998) idea of “musicking” and drawing from studies on place identity and place memory, the study focuses on how a local opera can strive towards new identity constructions through revitalising the forgotten local, historical past. Based on a purposive sample, the primary data set consists of semi-structured interviews and direct observation of the participants of the Kymi River Opera. Three thematic areas on the meanings of the opera, as conveyed by the participants, were identified in the abductive qualitative analysis: 1) Construction of a new place memory; 2) Equal possibility for participation; and 3) Integration of cultural politics and educational goals. The findings show the political nature of local opera in describing how the Kymi River Opera has become an arena for the politics of memory and place-making after a municipal merger in the 1990s resulted in a sense of loss of local identity.